2009
DOI: 10.1007/s00421-009-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat balance and cumulative heat storage during exercise performed in the heat in physically active younger and middle-aged men

Abstract: On separate days, eight physically active younger (22 +/- 2 years) and eight highly trained middle-aged (45 +/- 4 years) men matched for physical fitness and body composition performed 90 min of semi-recumbent cycling at a constant rate of heat production (290 W) followed by 60 min of seated recovery in either a temperate (T, 30 degrees C), warm (W, 35 degrees C) or hot (H, 40 degrees C) ambient condition. Rectal temperature (T (re)) was measured continuously, while the rate of whole-body heat loss (H (L)), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…The change in body heat content was, however, similar during R2, R3, and R4 in all age groups. This study was the first to show that in accordance with results obtained in young adults (21)(22)(23), even older adults have a compromised ability to dissipate heat during postexercise recovery, irrespective of the age-related impairments in thermoregulatory function observed during exercise. Hellon et al (12) and Lind et al (26) previously reported that sweat loss during the postexercise recovery periods tended to be greater in middle-aged adults relative to young adults.…”
Section: Whole Body Heat Loss During Postexercise Recoverysupporting
confidence: 58%
See 3 more Smart Citations
“…The change in body heat content was, however, similar during R2, R3, and R4 in all age groups. This study was the first to show that in accordance with results obtained in young adults (21)(22)(23), even older adults have a compromised ability to dissipate heat during postexercise recovery, irrespective of the age-related impairments in thermoregulatory function observed during exercise. Hellon et al (12) and Lind et al (26) previously reported that sweat loss during the postexercise recovery periods tended to be greater in middle-aged adults relative to young adults.…”
Section: Whole Body Heat Loss During Postexercise Recoverysupporting
confidence: 58%
“…Again, it is well established that core and skin temperature measurements underestimate changes in mean body temperature (17)(18)(19) and that these measurements do not accurately represent the magnitude of residual heat storage especially in the early stages (non-steady-state period) of exercise (2,19). As demonstrated by a growing number of recent studies (6,8,21,23), the use of whole body calorimetry is the optimal way to assess changes in whole body heat loss capacity and heat storage to eliminate the potential confounding effects of regional variations in local heat loss responses and heat distribution when studying independent groups. In fact, had we only relied on measurements of local sweating and skin blood flow, as well as core/skin temperature, our conclusions would have been markedly different, that is, the capacity to dissipate heat appears unaffected by advancing age.…”
Section: Whole Body Calorimetry Vs Local Heat Loss and Body Core Temmentioning
confidence: 96%
See 2 more Smart Citations
“…The HC of the body was defined as the energy required to increase the body temperature by 1 °C. Since the HC of fat (1.88 kJ/kg/°C) is lower than that in fat-free tissues (3.72 kJ/kg/°C), 37 200 kJ of H load after 90 minutes of intensive exercise 38 induces a temperature increment of 0.83 °C in a body of 70 kg weight with 15% fat, whereas the increment is 0.90 °C in the same weight of body with 30% fat.…”
Section: Heat Load and Sasang Typologymentioning
confidence: 99%